A Case of Aortic Dissection Presenting with Atypical Symptoms and Diagnosed with Transthoracic Echocardiography - Mahdis Solhjoo; Supreeya Swarup; Amgad N. Makaryus (Case Reports in Radiology)
We present a case of an extensive aortic dissection (AD) identified in a woman with atypical symptoms. Transthoracic echocardiography (TTE) allowed the identification of an intimal flap in multiple locations and resulted in rapid diagnosis and treatment. In most cases, CT angiography is the imaging modality of choice for diagnosis of AD. TTE is rapid and accurate and can be used in kidney failure. Our case highlights the important role of bedside echocardiography in the diagnosis of AD, especially in the patient with a typical symptoms in whom this diagnosis of AD may not be entertained and actually missed leading to negative and possibly deadly consequences.